Gender and level of education as determinants of cataloguers' computer information processing skills (2009)
Cataloguing operations are being computerized all over the world. Most cataloguers are not able to use this technology effectively. Previous studies had identified gender and level of education as probable factors that could affect the use of computers. This study, therefore, investigated the extent to which gender and level of education determined cataloguers’ computer information processing skills at the Kenneth Dike Library, University of Ibadan Nigeria. The survey research design was adopted for this study, using the availability sampling technique to select fifty respondents for the study. An instrument was designed for the purpose of collecting data for the study. Chi-Square and Multiple Regressions were used to analyze data at 0.05 level of significance. The study established that both gender and level of education determined cataloguers computer information processing skills. The findings of this study have serious implications for the management of university libraries and for teacher education and policy.